DETERMINATION OF SALIVARY URIC ACID LEVELS IN PERIODONTITIS AND HEALTH: A CASE CONTROL STUDY - Shetty, Mamatha; Talaviya, Dipen (Journal of Health and Allied Sciences NU, 2012)
The aim of this case-control study was to determine whether periodontitis was associated with impaired salivary antioxidant uric acid level. Sixty patients attending a routine dental check-up at department of periodontics AB Shetty memorial institute of dental science were recruited for the study. Thirty patients with periodontitis (case) and 30 patients with healthy periodontium (control) were included in the study. Periodontitis was defined as clinical attachment loss (CAL) ≥ 3mm in 30% of total sites examined (AAP-1999). CAL was measured from cemento-enamel junction to the base of pocket depth in mm using William's graduated probe. The teeth that was examined are (Ramfjord index teeth) 16, 21, 24, 36, 41, 44. l-2ml saliva was collected from patient in sterile glass vial and send for estimation of uric acid immediately. The uric acid level was measured in spectrophotometer. The result was statistically analyzed by student's t test. The mean value of uric acid level in periodontitis was 4.449 mg/dl.The mean value of uric acid level in healthy patient was 4.878 mg/dl. The study concluded that the level of uric acid in periodontitis patients was comparatively less than the normal patients. However, this difference was not statistically significant (p > 0.05)
Keywords: antioxidants; uric acid; periodontitis; saliva